Artillery Through the Ages: An etymology - Morton, Kevin (Lingua Frankly, 2014)
This paper examines the etymology of the word artillery, following its various uses throughout its history in the English language to discover how it entered common parlance and how its meaning has changed. Using the Oxford English Dictionary as the primary source for definitions and references to other works, the brief essay traces the word's evolution from a French loan to a naturalized English word. Multiple definitions are examined, with a number of its historical literary appearances addressed and explained. Textual references are largely culled from Middle English works from the 15th-17th centuries, though the essay ends with a brief discussion of the word's modern uses. Artillery seems to have undergone merely a narrowing of meaning in the centuries since its first appearance, and not a particularly drastic one; its current meaning is quite similar, or at least strongly related, to that of the 14th century.